Methicillin-resistant Staphylococcus aureus nasal colonization among adult patients visiting emergency department in a medical center in Taiwan. - Sheng-Yun Lu (Public Library of Science (PLoS), 2011)
Background Within the past 10 years, methicillin-resistant Staphylococcus aureus (MRSA) has not only been a hospital pathogen but also a community pathogen. To understand the carriage rate of methicillin-resistant Staphylococcus aureus (MRSA) among the adult patients visiting emergency department (ED), we conducted this study. Methodology/principal findings From May 21 to August 12, 2009, a total of 502 adult patients visiting emergency department (ED) of a tertiary care hospital in northern Taiwan were recruited in this study and surveyed for nasal carriage of MRSA. A questionnaire regarding the risk factors for MRSA acquisition was also obtained. The overall prevalence of MRSA nasal carriage among the patients was 3.8%. The carriage rate was significantly higher in patients with risk factors for MRSA acquisition (5.94%) than those without risk factors (2.12%). Patients with urinary complaints, diabetes mellitus, chronic kidney disease and current percutaneous tube usage were significantly associated with MRSA colonization. By multiple logistic regression analysis, only current usage of catheters or tubes was the independent predictor for MRSA nasal colonization. Of the 19 MRSA, most isolates belonged to one of two linages, characterized as sequence type (ST) 239 (32%) and ST 59 (58%). The latter linage, accounting for 83% of 6 isolates from patients without risk factors, is a community-associated (CA) clone in Taiwan, while the former linage is among healthcare-associated clones. Conclusion/significance A substantial proportion of patients visiting ED, particularly with current usage of percutaneous catheter or tubes, in northern Taiwan carried MRSA, mostly community strains, in nares.